Contribution Of Islamic Banks In Acceleration Of Halal Industry - hidaya, nurul (LP2M IAIN Palopo, 2023)
This study aims to analyze the contribution of Bank Muamalat in accelerating the halal industry. Where conventional banks dominate the market with higher figures compared to the market share of Islamic banks. This is seen as ironic, because the population of Indonesia is a population with the largest number of Muslims in the world. This reflects that public perception of Islamic banks is still minimal, especially regarding the Halal industry. The research method was carried out using a descriptive qualitative approach, data were collected by interviewing one person at Bank Muamalat and observation, then analyzed interactively (reduction, data presentation and drawing conclusions). The results of the study show that the contribution built by Bank Muamalat is able to build a different image in the eyes of consumers by providing accelerated products for the halal industry, namely back to back financing products, besides that the collaboration that is built is able to have a good impact on the economy and society